Bi2S3–In2S3 Heterostructures for Efficient Photoreduction of Highly Toxic Cr6+ Enabled by Facet‐Coupling and Z‐Scheme Structure. Issue 40 (25th August 2021) - Wang, Linjuan; Karuturi, Siva; Zan, Ling
Abstract: The construction of Z‐scheme photocatalyst materials mimicking the natural photosynthesis system provides many advantages, including increased light harvesting, spatially separated reductive and oxidative active sites and strong redox ability. Here, a novel Bi2 S3 nanorod@In2 S3 nanoparticle heterojunction photocatalyst synthesized through one‐pot hydrothermal method for Cr 6+ reduction is reported. A systematic investigation of the microstructural and compositional characteristics of the heterojunction catalyst confirms an intimate facet coupling between (440) crystal facet of In2 S3 and (060) crystal facet of Bi2 S3, which provides a robust heterojunction interface for charge transfer. When tested under visible‐light irradiation, the Bi2 S3 –In2 S3 heterojunction photocatalyst with 15% Bi2 S3 loading content achieves the highest Cr 6+ photoreduction efficiency of nearly 100% with excellent stability, which is among the best‐reported performances for Cr 6+ removal. Further examination using optical, photoelectrochemical, impedance spectroscopy, and electron spin resonance spectroscopy characterizations reveal greatly improved photogenerated charge separation and transfer efficiency, and confirm Z‐scheme electronic structure of the photocatalyst. The Z‐scheme Bi2 S3 –In2 S3 photocatalyst demonstrated here presents promise for the removal of highly toxic Cr 6+, and could also be of interest in photocatalytic energy conversion. Abstract : Bi2 S3 nanorods@In2 S3 nanoparticles heterostructure photocatalysts with facet‐coupling between Bi2 S3 (060) crystal facet and In2 S3 (440) crystal facet and Z‐scheme structure are reported. The heterostructure photocatalyst presents superior photoreduction efficiency among the reported photocatalysts, achieving nearly 100% Cr 6+ photoreduction under visible light illumination.